The Effect of Emotional Intelligence and Organizational Commitment on Employee Performance Through Work Motivation - Hutapea, Aturma; Nurhayati, Mafizatun (International Journal of Indonesian Business Review, 2022)
AbstractThis study aims to analyze the effect of emotional intelligence and organizational commitment on employee performance mediated by work motivation. The object of this research is the employee of the General Election Commission (KPU) Toba Regency. Determination of the sample in this study using a saturated sampling technique, so that all employees became respondents as many as 42 respondents and all respondents filled out the questionnaire. This research was conducted from January 2021 to April 2021 at the General Election Commission (KPU) Office ofToba Regency. The data were analyzed using Partial Least Square analysis. The results of this study indicate that emotional intelligence, organizational commitment and work motivation have a positive and significant effect on employee performance. Meanwhile, work motivation mediates emotional intelligence and organizational commitment to employee performance. Work motivation mediates emotional intelligence and organizational commitment perfectly, which is positive and significant.Keywords: Emotional Intelligence, Organizational Commitment, Work Motivation, Employee Performance